Methyl Gallate and Amoxicillin-Loaded Electrospun Poly(vinyl alcohol)/Chitosan Mats: Impact of Acetic Acid on Their Anti-Staphylococcus aureus Activity - Pimsumon Jiamboonsri; Weradesh Sangkhun; Sompit Wanwong (Polymers, 2024)
(MSSA) and MRSA. The formulation was optimized, and the impact of acetic acid on antibacterial activity was evaluated using agar disc diffusion. The final formulation was fabricated and characterized using SEM, FTIR, DSC, swelling, and release behavior analyses to understand its antibacterial efficacy. Results revealed that acetic acid eliminated antibacterial activity, but MG (64 mg/mL) and Amox (2.5 mg/mL) were successfully incorporated into a PVA/CS solution prepared with deionized water. The resulting nanofiber mats featured nanoscale fibers (126 ± 45 nm) with and micron-oval beads. Despite the in vitro synergism, the MG/Amox/PVA/CS mats showed no significant improvement over MG or Amox alone against MRSA, likely due to their physicochemical properties. FTIR and DSC results confirmed molecular interactions between the active compounds and the polymer matrix, which may cause a minimal swelling and low drug release at 24 h. This study offers insights into the potential of MG/Amox-loaded nanofibers for anti-MRSA material development.
Keywords: Electrospun Nanofibers in Biomedical Applications; Antimicrobial agents and applications; Nanocomposite Films for Food Packaging